Pengaruh Keikutsertaan Dalam Kelas Ibu Hamil Terhadap Rentang Waktu Penggunaan Kontrasepsi di Puskesmas Umbulharjo I, Yogyakarta Tahun 2016 - Riska Ismawati Hakim; Dyah Noviawati Setya Arum; Tri Maryani (POLTEKKES KEMENKES YOGYAKARTA, 2018)
Contraceptive use is a problem that may contributes to maternal mortality. The rate of unmeet-need according to the 2012 Demographic Health Survey of Indonesia is 8.5%. The high unmeet-need for family planning services will likely lead to the incidence of unwanted pregnancy. Unwanted pregnancy in post-partum mothers will lead to a very short pregnancy spacing and likely lead to abortion complications. Yogyakarta City is an area with the least new and active family planning participants in the province of Yogyakarta Special Region, with the lowest percentage is in Umbulharjo I Primary Healthcare Centre by 1.63% and 72.49%. Meanwhile, antenatal class program in which one of the materials contains postpartum birth control has been implemented in all public health centers in Yogyakarta city, one of which is in Umbulharjo I Primary Healthcare Centre, in accordance with the guidelines for the implementation of the antenatal class. This research aims to identify the effects of participation in antenatal class on the time range of contraceptive use. It belongs to an observational analytical research with cross sectional design to 173 respondents taken using purposive sampling and analyzed using Chi-Square Test. Of the 173 respondents, it was found out that the majority of participation in pregnant women class did not meet the standard, numbering 109 mothers (63%) and the time range of contraceptive use was not according to the standard (> 42 days), numbering 96 mothers (55.5%). The results of analysis using Chi-Square test indicated p-value = 0.04 (p = <0.05). This research concludes that there is an effect of participation in antenatal class on the time range of contraceptive use at Umbulharjo I Primary Healthcare Centre of Yogyakarta in 2016.